Gender Features of Euphemism in English and Uzbek Language - Rakhmanova Sarvinoz Alisherovna (Zien Journals, 2022)
The article deals with the gender features of Euphemism in English and Uzbek languages used by male and female members of Uzbek and English society and analyzes lexical-semanctic classification of the euphemic agents in each group. Furthermore, it is found beneficial for exploring the role of gender while determining the similarities and differences between the two languages used euphemisms. As we know, A Euphemism is an innocuous word or expression used in many different situations in order to say something in a polite way. But Euphemism are used by female and male differently. By the helping of the article, it can be clearified the difference of usage
Keywords: clearified; members; Furthermore; beneficial